Linguistic discrimination to victims of forced sterilizations in the access to justice from migratory linguistics - Marquina Praelli, José Alejandro (2022)
Linguistic discrimination generates inequality, and this is manifested in the lack of responses to meet the legal demands of a sector of the population. The legal case on forced sterilizations during the government of Alberto Fujimori is analyzed in this paper, with emphasis on the suspension of a hearing due to the lack of interpreters of Quechua, the language spoken by several of those affected. The main objective of the work is to analyze expressions related to linguistic discrimination in access to the justice service in Peru. The methodology consists of collecting data from social networks and news portals of Peruvian newspapers about the aforementioned case. Subsequently, the data obtained is analyzed by a theoretical framework where the pertinent concepts regarding linguistic discrimination, linguistic law, migratory linguistics and discourse analysis are exposed. Finally, the conclusions and corresponding bibliographical references are mentioned.